ANTIMICROBIAL AND ANTIOXIDANT ACTIVITIES OF TWO ENDOPHYTIC FUNGI ISOLATED FROM MELASTOMA MALABATHRICUM L. LEAVES - Sarbadhikary, Sunrit Basu; Pal, Balaram; Mandal, Narayan C. (International Journal of Current Pharmaceutical Research, 2016)
Objective: The objectives of this study were to isolate endophytic fungi from Melastoma malabathricum L. leaves and to study their antimicrobial and antioxidant potentials. Methods: Disc diffusion method and Agar well diffusion method was carried out for studying the antibacterial and antifungal range of the isolated endophytes MMF5 and MMF9. DPPH (2, 2-diphenyl-2-picrilhydrazyl) reduction assay was followed for the study of antioxidant activities of the isolated. CFU counting method was followed for determining the MICs of the isolates against two selected bacteria and to know the mode of action. Results: Two endophytic fungi have been isolated which were identified as species of Penicillium by studying their morphology under a compound light microscope. Both were found to show great antibacterial activities against Gram-negative as well as Gram-positive bacteria. The Minimum Inhibitory Concentration (MIC) value of the ethyl acetate extracts of MMF5 and MMF9 were found to be 150Âµg/ml and 100Âµg/ml respectively for Staphylococcus aureus and Escherichia coli with the bacteriostatic mode of action. They also exhibited good antifungal activities against an animal as well as plant pathogenic fungi. IC50 value of MMF5 and MMF9 in an antioxidant assay using stable DPPH radical was found to be 52.38Î¼g/ml and 24.44Î¼g/ml respectively in comparison to the control ascorbic acid having the value 8.5Î¼g/ml. Conclusion: From this study, it can be said that due to having good antimicrobial and antioxidant activities, the strains can be used as a prospective source in the medicinal industry for the drug development.